Mixed Spinel Co0.4Zn0.6Fe2O4 Ferrite Nanoparticles As a Magnetic Photocatalyst: Synthesis and Dye Degradation - Sami, We'am (Iraqi Journal of Science, 2023)
In this paper, mixed spinel Co0.4Zn0.6Fe2O4 ferrite was synthesized by microwave-assisted combustion method. Photocatalytic activity of the as-synthesized sample was investigated against methylene blue dye at room temperature at different exposure times (60-360 min.) under visible light. Phase impurity and surface morphology which are investigated with XRD analysis and field emission- scanning electron microscopy, indicate that a cubic spinel unit cell structure with a crystilite size and lattice constant are 22.5048nm and 8.37Å, respectively. The saturation magnetization exhibited directly from the hysteresis loop is (70.20emu/g). Optical properties for the investigated ferrites exhibited photo absorption from UV to visible region with an energy gap of (1.6 eV). Mainly two broad metal-oxygen bands for spinel Co0.4Zn0.6Fe2O4 ferrite  photocatalyst are seen in FT-IR spectra. The degradation ratio of dye increased as exposure time was increased .